2009
DOI: 10.1074/jbc.m109.020230
|View full text |Cite
|
Sign up to set email alerts
|

A G-quadruplex Stabilizer Induces M-phase Cell Cycle Arrest

Abstract: G-quadruplex stabilizers such as telomestatin and HXDV bind with exquisite specificity to G-quadruplexes, but not to triplex, duplex, or single-stranded DNAs. Studies have suggested that the antiproliferative and possibly anti-tumor activities of these compounds are linked to their inhibitory effect on telomerase and/or telomere function. In the current studies, we show that HXDV, a synthetic analog of telomestatin, exhibits antiproliferative activity against both telomerase-positive and -negative cells and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 51 publications
(66 reference statements)
3
28
0
Order By: Relevance
“…7c HXDV has moderate cytotoxicity towards tumors cells (average IC 50 ~0.5 μM), which is comparable to that reported for telomestatin 8. HXDV induces robust apoptosis in both telomerase positive and telomerase negative cells within 16 h, causes M-phase cell cycle arrest, and reduces the expression of the M-phase checkpoint regulator Aurora A 9. These effects are not observed for the non-G-quadruplex stabilizing 24-membered macrocycle TXTLeu (tetraoxazoletetraleucine, Figure 1).…”
Section: Introductionsupporting
confidence: 68%
“…7c HXDV has moderate cytotoxicity towards tumors cells (average IC 50 ~0.5 μM), which is comparable to that reported for telomestatin 8. HXDV induces robust apoptosis in both telomerase positive and telomerase negative cells within 16 h, causes M-phase cell cycle arrest, and reduces the expression of the M-phase checkpoint regulator Aurora A 9. These effects are not observed for the non-G-quadruplex stabilizing 24-membered macrocycle TXTLeu (tetraoxazoletetraleucine, Figure 1).…”
Section: Introductionsupporting
confidence: 68%
“…While a previous report suggested that the reduction in the Aurora A protein level during a G-quadruplex stabilizer-induced cell cycle arrest may result from the stabilization of a potential RNA G-quadruplex in its 5' UTR, no direct evidence was provided to support the formation of this RNA G-quadruplex and the role of this sequence in cell cycle regulation. 66 We demonstrated in this study that the CRQ RNA G-quadruplex within the 5' UTR of CCND3 plays a role in the G1/S phase transition of the cell cycle. Mutations that disrupt the formation of the G-quadruplex structure led to the production of more CCND3 protein from the expression vectors, which promoted the phosphorylation and inactivation of the Rb tumor suppressor gene and subsequently resulted in accelerated cell cycle progression and cell proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…This is elegantly demonstrated by the recent advances in time-resolved cryo-electron microscopy, based on insights from single-molecule fluorescence measurements. The studies provided a detailed insight into the structure of the ribosome in real time as it transitions through different functional states during protein biosynthesis (Fischer et al, 2010;Tsai et al, 2014;Chen et al, 2015;Belardinelli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%